New dimension in vortex electro-magnetic wave transmission with orbital angular momentum - Chao ZHANG; Yuanhe WANG (Tongxin xuebao)
Purpose:The vortex Electro-Magnetic (EM) wave transmission system with Orbital Angular Momentum (OAM), which is the potential key technology in future mobile communications,is easily confused with the traditional Multiple-Input Multiple-Output (MIMO) transmission system. This leads to the controversy on whether the OAM of vortex EM waves can provide the new dimension for the wireless transmission. This paper points out that only the vortex EM wave transmission system with vortex photons carrying Intrinsic OAM(IOAM)can obtain the new dimension.Furthermore,compared with the MIMO transmission with multiple antennas,Extrinsic OAM(EOAM)formed by the plane microwave photons in the statistical OAM beam is coupled with the space domain and cannot provide additional new dimension. Method:This paper analyzes the physical characteristics of the EM wave with OAM and traces back to the history of the EM wave resource utilization and development. Moreover, the formula of Shannon channel capacity containing OAM dimension is given, and the significance of power multiplexing of new dimension for capacity enhancement is specified. In order to show the insight of the new dimensional characteristics of vortex EM waves, the typical vortex EM wave OAM transmission systems are classified into four different regions according to the channel capacity. Taking the microwave band as an example,it is pointed out that only the quantum OAM vortex EM wave transmission based on vortex microwave photons can surpass the traditional multi-antenna MIMO capacity bound and form a new MIMO capacity bound containing the OAM dimension. Consequence:In order to illustrate the application scope and the outstanding advantages utilized by quantum OAM electromagnetic waves and statistical OAM Beams, this paper classifies the typical OAM transmission systems into four regions based on channel capacity.From the high channel capacity to the low channel capacity, Region A belongs to the quantum OAM transmission system with the new dimension of OAM, using vortex microwave photon to convey information, and the corresponding capacity bound can be enhanced to surpass the traditional multi-antenna MIMO capacity bound;Regions B,C and D belong to the statistical OAM vortex beams,which do not own new dimensions in MIMO transmission but have outstanding performance in the Line-of-Sight (LoS) channel. Compared with the traditional LoS MIMO transmission, Region B refers to the OAM dedicated antenna transmission system, which can recover the channel orthogonality and the rank of the channel matrix,so that a significant capacity enhancement is obtained,which represents the development trend of statistical OAM vortex beam.Region C refers to the array antenna full-phase plane transmission system.It enjoys low system complexity and high technical maturity as a representative of early OAM technology. Region D refers to the partial phase transmission system, which does not need to receive the complete phase plane, and is suitable for long-distance transmission. Conclusion:In response to the controversy on whether OAM electromagnetic waves can provide the new dimension for the wireless transmission, this paper analyzes the physical insight of the EM wave transmission with OAM in history.It can be concluded that:both the intrinsic OAM and the extrinsic OAM can be utilized by EM waves,but only quantum OAM vortex microwave photons transmission based on intrinsic OAM can generate new dimensions in the wireless transmission besides the MIMO transmission. The statistical OAM vortex beams based on extrinsic OAM cannot constitute new dimensions beyond MIMO transmission and just belongs to the special case of multi-antenna MIMO systems which can generate the beams with helical phase front.